PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 017 SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Rayani, Mira (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research was motivated by the low science learning outcomes ofstudents, with an average value of 63.7 class. While the value of minimumcompleteness criteria (KKM) IPA 65. This research is a classroom actionresearch (CAR). Aims to improve science learning outcomes fourth grade studentsof SDN SDN 017 Segajah River Kubu district of Rokan Hilir. Formulation of theproblem: Is the application of problem solving learning model to improvelearning outcomes IPA 017 fourth grade students of SDN Segajah River Kubudistrict of Rokan Hilir. Data were collected through observation using theobservation sheet, for learning outcomes data through UH UH I and II. Studentlearning outcomes prior to action by an average of 63.7 after one cycle increasedby an average of 70.5% with enough categories and the second cycle with anaverage of 83.75% with both categories. So improving student learning outcomesof basic score kesiklus an increase of 6.8% from the base score kesiklus while twoincreased to 20.05%. While the activities of students in the first cycle was 57.14%,and the second cycle was 74.99%. While teachers have 60.71% in the first cycleand the second cycle was 78.57. These results prove that the application ofLearning Model of Problem Solving Can Improve Student Learning OutcomesIPA SDN 017 Class IV river Segajah Kubu district of Rokan Hilir.Keywords: Problem Solving, IPA leaning outcome